Determinant Analysis of SAKTI Implementation (Delone and Mclean Information System Success Model Approach) - Miftahul Hadi; Ambarwati, Ria Dewi; Hari Sugiyanto; Anjahul Khuluq (Riset Akuntansi dan Keuangan Indonesia, 2024)
Currently,the process of budgeting, expenditure budget execution and reporting the state revenue and expenditure budget in ministries/agencies uses an integrated information system. Using an integrated system, all data is available in an information system and can be accessed easily, faster and more safely. This study aims to analyze how successful the implementation of web-based SAKTI pilot project. The data used comes from a questionnaire on the number of respondents who obtained 244 samples from 10 ministries/ government agencies. Data analysis used descriptive statistical analysis and Structural Equation Model-Partial Least Square (SEM-PLS) using R-Studio and WarpPLS 7.0 software. According to the findings, system quality, information quality, service quality all had a positive significant effect on user satisfaction and user satisfaction had a significant and positive effect on net profit. Based on the results of the hypothesis, it can be concluded that the implementation of the SAKTI piloting has been going well and according to user expectations.